Mutated Random grid Approach to Share Secret Image into Visually Pleasing Shares - kumarJatav, Jasvant; Kannojia, Suresh Prasad (International Journal of Computer Sciences and Engineering, 2021)
Visual cryptography is a technique to diffuse and disguise a secret image into a 2D pattern of black and white pixels, called shares. Individual or any k-1 shares have no clue about the secret image, but any k shares out of n, can decode the secret image. These meaningless shares are subject to suspect for the intruders. Stacking of shares reconstructs the secret image populated with noisy pixels. In addition to these traditional visual cryptography suffer with pixel alignment problem. To resolve these problems this paper proposes a (2, 2) mutated random grid approach to share a secret image into visually pleasing shares. The solution to the problem is based on assignment of instances of random two dimensional matrix of binary numbers and its XOR operation with respective pixels with auxiliary gray image. It requires lightweight computing device to decode the secret image. Comparative analysis of the experimental results with that of existing fundamental approaches shows that proposed approach performs better.